Heuristics in decision-making by exporting textiles SMEs. Issue 1 (2nd January 2021) - Guercini, Simone; Runfola, Andrea
ABSTRACT: This article deals with the use of heuristics in the decision-making process of entrepreneurial exporting Small and Medium-Sized Enterprises (SMEs) in business-to-business settings. It specifically considers the textile industry. Heuristics can be defined as "simple rules" for cognition and action. The article points out the presence of a research gap in the literature on the decision-making of exporting SMEs and deals with the following research question: What heuristics are used in exporting decisions by SMEs in business-to-business markets? Empirically, it discusses the findings of seven case studies of Italian exporting textiles SMEs in business-to-business markets. The results reveal the widespread use of heuristics and formulate propositions about their features. Findings show that heuristics in exporting SMEs in the textile industry are perceived as effective tools for export decisions, corresponding to personal beliefs of the single decision-maker, intentionally built through experience, generalizable to different export markets, and time tested.